The 1951 United Nations Convention Relating to the Status of Refugees - Béres, Nóra (The Universal Protection of Human Rights, 2026)
Abstract: This chapter seeks to provide the readers with a brief overview of the key elements of the Refugee Convention. To this end, the definition of “refugee” will be analysed first of all, where the so-called inclusion, exclusion and cessation criteria will be scrutinised with due consideration. Within the framework of assessment of the inclusion element, the meaning of ‘being outside the country of his nationality’, well-founded fear, persecution, and of the five limitative grounds as motives of persecution will be highlighted. Secondly, refugee rights will be examined within a comparison of refugee rights and human rights. For the third pillar of this chapter, the principle of non-refoulement will be addressed as a cornerstone of international refugee law. Concluding remarks will also be added in closing this chapter.Keywords: asylum, non-refoulement, refugee, UNHCR, Refugee Convention